Oxidation of Porphyrins in the Presence of Nucleophiles: From the Synthesis of Multisubstituted Porphyrins to the Electropolymerization of the Macrocycles - Schaming, Delphine; Giraudeau, Alain; Ruhlmann, Laurent; Allain, Clémence; Hao, Jian; Xia, Yun; Farha, Rana; Goldmann, Michel; Leroux, Yann; Hapiot, Philippe (IntechOpen, 2011)
None